A case-crossover study of occupational laceration injuries in pork processing: methods and preliminary findings. Issue 10 (13th September 2010) - Lander, Lina; Sorock, Gary S; Stentz, Terry L; Eisen, Ellen A; Mittleman, Murray; Hauser, Russ; Perry, Melissa J
Abstract : Objectives: Meatpacking remains a hazardous and largely unexamined industry. Despite prevention efforts, laceration injuries, among others, remain high. We estimated the magnitude of associations between transient exposures such as equipment malfunction, performing an unusual work task, rushing, and occurrence of laceration injuries. Methods: Injured workers were recruited from two pork-processing plants, one in Iowa and one in Nebraska. A telephone interview was conducted within 7 days of the injury, on average to collect information on fixed and transient exposures preceding the injury event. Case-crossover methodology was used to evaluate case and control data within the same subject, thus controlling for between-subject confounding. A Mantel–Haenszel estimator for person-time data was used to estimate the relative risks of injury and transient exposures of interest. Results: Of the 362 workers with lacerations between April 2006 and October 2007, 153 (42%) were interviewed (74% male, 41% Hispanic). Forty-eight per cent were injured by a knife or a knife-like object such as scissors or a band saw. Other sources of lacerations included sharp edges and hooks. Tool sharpening was associated with the highest RR of laceration (RR 8.4, 95% CI 5.4 to 12.8) followed by slipping (RR 74.8, 95% CI 30.5 to 183.3), equipment malfunction (RR 3.8, 95% CI 2.8 to 5.3), and performing an unusual task (RR 3.7, 95% CI 2.6 to 5.2). Being tired, distracted, or rushing were not significant risk factors for a laceration. Conclusions: Aspects of the physical environment and work practices appear to be significant risk factors for laceration injury in meatpacking. Personal risk factors were less significant in this study.